Mengkritisi Predikat Provinsi Daerah Istimewa Yogyakarta sebagai Provinsi Termiskin di Pulau Jawa - Permatasari, Ane (Universitas Sultan Ageng Tirtayasa, 2024)
Based on data released by the Central Bureau of Statistics, Yogyakarta Special District Province (hereinafter called DIY Province) is categorized as the poorest province on the island of Java with a poverty rate of 12.8% well above the national figure of 10.6%. Without intending to ignore the data, this study is intended to criticize the prejudice received by DIY Province because at the same time DIY Province is ranked as the province with the longest life expectancy and the highest happiness index compared to other provinces in Indonesia. The method used is a qualitative research method with data collection techniques using documentation techniques that are then analyzed with content analysis methods that are cross-checked with interviews. Based on the results of research found that there are cultural values in DIY province that make the poverty indicators used by BPS need to be perceived more widely.